Comparative research on two equivalent mechanical models of liquid sloshing in tanks. (2018) - Yu, Di; Chu, Jiangwei
Using a quasi-static model, it was found that the mass centre of the liquid trajectory is the same as the length-width ratio of the ellipse of the tank. According to the principle of mechanical equivalence, two types of equivalent mechanical models of liquid sloshing in a tank were established, and the relevant parameters of the two models were derived. The simulation results show that the two models can more accurately describe the linear motion of liquid sloshing. The fluid dynamics simulation results of tank liquid vibration frequency division were compared with those obtained using ANSYS Fluent software under similar conditions; it was concluded that the model is more suitable for a liquid vibration frequency range. A simulated test bench was used to verify the two models; the results show the pendulum model is more suitable.